Highly conformal CT based surface mould brachytherapy for non-melanoma skin cancers of earlobe and nose - Kuncman, Łukasz; Kozłowski, Sławomir; Pietraszek, Andrzej; Pietrzykowska-Kuncman, Malwina; Danielska, Justyna; Sobotkowski, Janusz; Łuniewska-Bury, Jolanta; Fijuth, Jacek (Journal of Contemporary Brachytherapy, 2016)
Purpose : Brachytherapy (BT), due to rapid dose fall off and minor set-up errors, should be superior to external beam radiotherapy (EBRT) for treatment of lesions in difficult locations like nose and earlobe. Evidences in this field are scarce. We describe computed tomography (CT) based surface mould BT for non-melanoma skin cancers (NMSC), and compare its conformity, dose coverage, and tissue sparing ability to EBRT. Material and methods: We describe procedure of preparation of surface mould applicator and dosimetry parameters of BT plans, which were implemented in 10 individuals with NMSC of nose and earlobe. We evaluated dose coverage by minimal dose to 90% of planning target volume (PTV) (D 90 ), volumes of PTV receiving 90-150% of prescribed dose (PD) (VPTV 90 -150), conformal index for 90 and 100% of PD (COIN 90 , COIN 100 ), dose homogeneity index (DHI), dose nonuniformity ratio (DNR), exposure of organs. Prospectively, we created CT-based photons and electrons plans. We compared conformity (COIN 90 , COIN 100 ), dose coverage of PTV (D 90 , VPTV 90 , VPTV 100 ), volumes of body receiving 10-90% of PD (V 10 -V 90 ) of EBRT and BT plans. Results : We obtained mean BT-DHI = 0.76, BT-DNR = 0.23, EBRT-DHI = 1.26. We observed no significant differences in VPTV 90 and D 90 between BT and EBRT. Mean BT-VPTV 100 (89.4%) was higher than EBRT-VPTV 100 (71.2%). Both COIN 90 (BT-COIN 90 = 0.46 vs. EBRT-COIN 90 = 0.21) and COIN 100 (BT-COIN 100 = 0.52 vs. EBRT-COIN 100 = 0.26) were superior for BT plans. We observed more exposure of normal tissues for small doses in BT plans (V 10 , V 20 ), for high doses in EBRT plans (V 70 , V 90 ). Conclusions : Computed tmography-based surface mould brachytherapy for superficial lesions on irregular surfaces is a highly conformal method with good homogeneity. Brachytherapy is superior to EBRT in those locations in terms of conformity and normal tissue sparing ability in high doses.